2009
DOI: 10.4049/jimmunol.0804033
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen Synthase Kinase-3β Facilitates IFN-γ-Induced STAT1 Activation by Regulating Src Homology-2 Domain-Containing Phosphatase 2

Abstract: Glycogen synthase kinase-3β (GSK-3β)-modulated IFN-γ-induced inflammation has been reported; however, the mechanism that activates GSK-3β and the effects of activation remain unclear. Inhibiting GSK-3β decreased IFN-γ-induced inflammation. IFN-γ treatment rapidly activated GSK-3β via neutral sphingomyelinase- and okadaic acid-sensitive phosphatase-regulated dephosphorylation at Ser9, and proline-rich tyrosine kinase 2 (Pyk2)-regulated phosphorylation at Tyr216. Pyk2 was activated through phosphatidylcholine-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
75
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 84 publications
(134 reference statements)
9
75
1
Order By: Relevance
“…Studies in our laboratory have shown that glycogen synthase kinase (GSK)-3b has a suppressive role on SHP2 phosphorylation, while pharmacologically inhibiting GSK-3b facilitated SHP2 activation followed by SHP2-mediated IFN-g resistance (36,65). Notably, in H. pylori infection, PI3K/Akt signaling may inactivate GSK-3b followed by b-catenin stabilization to promote gastric tumorigenesis (66,67).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in our laboratory have shown that glycogen synthase kinase (GSK)-3b has a suppressive role on SHP2 phosphorylation, while pharmacologically inhibiting GSK-3b facilitated SHP2 activation followed by SHP2-mediated IFN-g resistance (36,65). Notably, in H. pylori infection, PI3K/Akt signaling may inactivate GSK-3b followed by b-catenin stabilization to promote gastric tumorigenesis (66,67).…”
Section: Discussionmentioning
confidence: 99%
“…To detect the expression of E-cadherin, IFNGR1, IFNGR2, CagA, phosphorylated SHP2 (Tyr 542 ), and SHP2, we fixed, stained, and analyzed the cells as described previously (36). Cells were stained with primary Abs and then incubated with a mixture of Alexa Fluor 488-or 594-conjugated goat anti-mouse or rabbit IgG.…”
Section: Immunostainingmentioning
confidence: 99%
See 1 more Smart Citation
“…shRNA clones were obtained from the National RNAi Core Facility, Institute of Molecular Biology/Genomic Research Center, Academia Sinica (Taipei, Taiwan). Lentiviruses were prepared, and cells were infected, according to previously described protocols (55).…”
Section: Rna Interferencementioning
confidence: 99%
“…The proapoptotic and proinflammatory properties of GSK-3 have also been demonstrated in various animal models of inflammation, including experimental lung injury, shock, spinal cord trauma, arthritis, ischemia/reperfusion injury, infection, asthma, colitis, renal failure, and hepatotoxicity (36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). GSK-3 is currently a known regulator of IFN-g signaling and is involved in IFN-g-induced inflammatory activation (51)(52)(53)(54)(55)(56)(57)(58)(59). Previous studies performed by ourselves and others identified a proinflammatory role for GSK-3 and found that inhibiting GSK-3 provides cellular protection against IFN-g (54-56)-, TNF-a (60)-, and LPS-induced inflammation in vitro (61)(62)(63) and multiple organ failure in vivo (46,47,49,63).…”
mentioning
confidence: 99%